Copper-catalyzed oxidative functionalization of benzylic C–H bonds with quinazoline 3-oxides. Issue 16 (19th July 2018) - Fan, Liwen; Zhang, Zhenming; Wang, Tao; Liang, Qingjin; Zhao, Junfeng
Abstract : A highly efficient copper-catalyzed oxidative functionalization of benzylic C(sp 3 )–H bonds with quinazoline 3-oxides has been developed. Abstract : A highly efficient copper-catalyzed oxidative functionalization of benzylic C(sp 3 )–H bonds with quinazoline 3-oxides was described. This protocol provides a broad range of quinazolin-4(3 H )-one derivatives in good to excellent yields using a Cu/TBHP oxidation system. A plausible reaction mechanism involving radical species is proposed to rationalize the experimental results.